Financial literacy on a person‘s attitude towards debt and the influence of friends on debt habits in Indonesia - nurhaliza, Siti; Daud, Iizar; malini, Helma; Giriati, Giriati; Irfani, Muhammad (SEAN Institute, 2024)
It is very important for each individual to have the insight and skills to be able to use the money they have effectively so as to provide optimal benefits. there is uncontrolled spending. The income earned by individuals can run out in a short time, so many individuals are looking for various alternative sources of income from various loan sources, both online and conventional banks. The research aims to analyze the influence of financial literacy on a person's attitude towards debt and the influence of friends on debt habits. The research method used is a literature review. This research shows that financial attitudes, peers, and financial literacy have a positive influence on financial management behavior, including debt.